STRATEGI GROUP INVESTIGATION UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS SISWA SMA - Padma Mike Putri M; Tatang Mulyana (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis research is based on the lack of mathematical reasoning skills of students. we need a strategy to encourage students to develop mathematical reasoning ability. Learning strategy group investigation allows students to develop mathematical reasoning skills. The aims of this study are to examine the improvement of mathematical reasoning abilities of students who get group investigation and students who get regular learning. Design of this studi is the design of a control group of non-equivalence in order to obtain samples of class X in one of SMA in Solok of two classes using purposive sampling technique. Instruments of this study includes tests of mathematical reasoning ability. Based on the analysis of information found that Improvement of student’s mathematical reasoning ability who got group investigation learning better than students who got the regular learning.Keywords: Mathematical Reasoning, Group Investigation Learning, Regular Learning